1989
DOI: 10.1080/02724936.1989.11748589
|View full text |Cite
|
Sign up to set email alerts
|

The effects on malaria of treatment of iron-deficiency anaemia with oral iron in Gambian children

Abstract: In order to determine whether giving iron to iron-deficient children increases their susceptibility to malaria, 213 Gambian children aged between 6 months and 5 years with iron-deficiency anaemia were randomized to receive either oral iron or placebo during the rainy season when malaria transmission is maximal. Haematological and iron measurements improved significantly in the group given iron. Regular morbidity surveys showed that fever associated with parasitaemia occurred more frequently in the iron-treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(37 citation statements)
references
References 19 publications
0
36
0
1
Order By: Relevance
“…35 It was not possible for us to distinguish the effects of dietary-related iron deficiency on anemia from those of malaria infection. Both mechanisms are likely to interact, 36 more so in a population with low intake of iron from the diet such as the one under study. 5 Associations between breastfeeding and anemia have been reported from cross-sectional studies.…”
Section: Discussionmentioning
confidence: 99%
“…35 It was not possible for us to distinguish the effects of dietary-related iron deficiency on anemia from those of malaria infection. Both mechanisms are likely to interact, 36 more so in a population with low intake of iron from the diet such as the one under study. 5 Associations between breastfeeding and anemia have been reported from cross-sectional studies.…”
Section: Discussionmentioning
confidence: 99%
“…Four studies were 2 3 2 factorial studies that were extracted as iron versus control and iron with another intervention versus that intervention alone with arms combined during meta-analysis. [25][26][27][28] Three studies [28][29][30] were cluster randomized trials, none of which reported that results as presented had been corrected for clustering (although Stoltzfus et al 28 reported that regression coefficients had been corrected). Intraclass correlation coefficients (ICCs) for Hb and ferritin in cluster trials have generally been found to be ,0.001 to 0.051, 31 which are sufficiently low that correction for sample size was not considered necessary in the 2 studies from which data for these outcomes were extracted (Bhatia and Seshadri 29 …”
Section: Study Characteristicsmentioning
confidence: 97%
“…On the other hand, risk of malaria is influenced by iron status and deficiency of iron protects children from malarial morbidity and mortality [13]. Several studies identify increased malarial risk in individuals treated with iron through mechanisms of rapid saturation of ironbinding proteins [14,15], but other studies suggest that standard doses of iron supplements do not increase the risk for malaria [16][17][18]. & Pica Pica, defined as a compulsive consumption of non nutritive substances, is a common symptom of IDA.…”
Section: Clinical Featuresmentioning
confidence: 99%